2020
DOI: 10.48084/etasr.3713
|View full text |Cite
|
Sign up to set email alerts
|

A Foresight Study about the Skills and Competencies Needed for Quality Professionals in 2030: An Empirical Study of Saudi Arabia

Abstract: This paper presents the results of a foresight study examining the future knowledge, skills, and competencies required by quality professionals to meet the goals and objectives of the Saudi Vision 2030. The study aims to develop a methodology allowing the forecasting of skills and competency demands in the future. Data collection was conducted through the design of a web-based questionnaire that was distributed online to academic and quality management specialists in Saudi Arabia. The questionnaire consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These studies play a significant role in enabling decisionmakers to develop strategies and solutions. Touahmia et al (2020) emphasize that, despite the growing research in the field of future studies, studies predicting future professions and the associated new skills remain limited. Within the scope of Saudi Arabia's efforts to provide the foundation for achieving Vision 2030 in education, some studies have been conducted.…”
Section: Statement Of Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies play a significant role in enabling decisionmakers to develop strategies and solutions. Touahmia et al (2020) emphasize that, despite the growing research in the field of future studies, studies predicting future professions and the associated new skills remain limited. Within the scope of Saudi Arabia's efforts to provide the foundation for achieving Vision 2030 in education, some studies have been conducted.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…The study recommended the necessity of equipping the human capital with skills and competencies that qualify them to deal with future professions and the associated challenges and changes. Touahmia et al (2020) conducted an exploratory study to identify the knowledge and skills associated with the future of specialists in quality fields. The study emphasized the importance of continuous research in exploring the skills and competencies necessary to deal with future challenges and associated professions.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Cutting-tool wear and consumption are considered subjects of major concern [2,3]. This is of major importance for air conditioning manufacturers and military industries in Saudi Arabia, which has invested heavily in such industries within its 2030 Saudi Vision [4,5,6,18]. It is estimated that the size of Saudi investments in the HVAC manufacturing sector stood at $3.7 billion in 2018 and is projected to grow up to reach $7.1 billion by 2024 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Limited foresight studies were reported from developed countries like Brazil, Columbia and Iran. Only, very limited studies were published in Arab countries like the MENA region, mainly in the Kingdom of Saudi Arabia and the UAE [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%